DIFFERENCES VALUE OF PT AND APTT IN EXAMINATION OF ELECTROMECHANICAL AND PHOTO-OPTICAL METHOD - Ramadhani, Beytri; Notopuro, Paulus B. (Journal of Vocational Health Studies, 2021)
Background: Examination of PT and APTT in hospitals and clinical laboratories by utilizing the use of different instruments and methods. Examination of PT and APTT can be implemented through electromechanical or photo-optical techniques to detect changes in plasma turbidity. This method principle isprincipled that addition can affect the increase in plasma viscosity. Purpose: To analyze the differences in the values of PT and APTT between the electromechanical method and the photo-optical method. Method: Analytical observation, 32 plasma citrate without interference and hemolysis were examined at the Clinical Pathology Laboratory of RSU Haji Surabaya and the Ultra Medica Main Clinics Laboratory in Surabaya. The study used SPSS 24.0 program to determine whether there were  PT and APTT values with an electromechanical and photo-optical method. Result: The result of PT and APTT with the electromechanical method was significantly higher than PT and APTT with the photo-optical method on samples without interference. In hemolytic samples, the result of PT with the electromechanical method was significantly higher than the PT result with the photo-optical method. Meanwhile, the result of APTT with the electromechanical method was significantly lower than the APTT result with the photo-optical method in hemolytic samples. Conclusion: There were significant differences in PT and APTT results between electromechanical and photo-optical in samples without interference and hemolytic. It is due to the difference in the detection principle between the two methods.